Indigenous Custodianship and Timber Legality Assurance System: Challenges and Opportunities for Customary Forest Management in Indonesia - Iriyani, Silfi; Arman, Muhammad; Nugroho, Bramasto; Buchori, Damayanti; Setiajiati, Fitta (Department of Forestry, Faculty of Agriculture, University of Lampung, 2024)
Indigenous peoples are caretakers and practitioners of a unique culture connected to their community and the surrounding environment, including forests. In Indonesia, existing regulations acknowledge the identity of indigenous peoples and the forests they oversee. This paper provided evidence of the acknowledgment of customary forests and indigenous peoples, addressing the challenges and opportunities for managing customary forest products, both timber and non-timber, under a timber legality assurance scheme. This research is essential in advocating for legal reforms that protect the rights of indigenous peoples and ensure sustainable forest management while balancing environmental conservation with local community needs. The study sought to illuminate the challenges Indigenous Peoples encounter when accessing and utilizing forests and forest products within their customary territories. It employed exploration methods to gather reliable data and information, validated through expert interviews and described using triangulation. The research concluded that legal innovations are necessary to resolve issues concerning the recognition of customary forests and indigenous peoples to enable effective forest management while safeguarding the rights of indigenous peoples socially, economically, and ecologically. In addition, legal innovations are also required to avoid breaches of timber legality assurance, which can result in forest unsustainability. To enhance the effectiveness of these reforms, it is important to foster collaboration between government bodies and indigenous communities in developing and implementing forest management policies. Keywords: customary forests, forest governance, indigenous peoples, timber legality assurance